2016
DOI: 10.1007/s00232-016-9915-0
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Effect Induced by Electroporation is Possibly Mediated by Microvesicles and Dependent on Pulse Amplitude, Repetition Frequency and Cell Type

Abstract: Bystander effect, a known phenomenon in radiation biology, where irradiated cells release signals which cause damage to nearby, unirradiated cells, has not been explored in electroporated cells yet. Therefore, our aim was to determine whether bystander effect is present in electroporated melanoma cells in vitro, by determining viability of non-electroporated cells exposed to medium from electroporated cells and by the release of microvesicles as potential indicators of the bystander effect. Here, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The increase in uptake of PI after electroporation was used as an indicator of electropermeability of cells. The measurement of median fluorescence and percentage of PI-positive cells was carried out with FACSCanto II flow cytometer (BD Biosciences) as described by Prevc et al (27).…”
Section: Methodsmentioning
confidence: 99%
“…The increase in uptake of PI after electroporation was used as an indicator of electropermeability of cells. The measurement of median fluorescence and percentage of PI-positive cells was carried out with FACSCanto II flow cytometer (BD Biosciences) as described by Prevc et al (27).…”
Section: Methodsmentioning
confidence: 99%
“…The bystander effect after irreversible electroporation was analyzed in a recent study [ 53 ]. Contrary to our results, this study reported a slight negative bystander effect after IRE, showing that the viability of B16 cells, but not CMeC-1 cells, decreased by around 16%.…”
Section: Discussionmentioning
confidence: 99%
“…The medium from the affected cells was taken from one well (one experiment point) 24 h post electric field application and added to the wells with unaffected cells. Cell viability was measured after 24 h with Presto Blue reagent [ 53 ]. In our experiments, the affected medium was collected from 10 wells (10 experiment points) after 24 h of incubation, and the viability was evaluated by using the clonogenic assay 6 days after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EP can also induce a bystander effect, seen when using conditioned medium, possibly through the release of microvesicles, with a decrease of viability in the cell lines exposed to medium from RE and IRE treated cells. The number of microvesicles and the induction of cell death upon exposure to the conditioned medium are increased as the electric field intensity and the number of applied pulses rise, and also varies according to cell type [ 128 ].…”
Section: Immunological Aspects Of Reversible Electroporation and Electrochemotherapymentioning
confidence: 99%